Abreviasi pada berita daring bertopik covid-19 dalam negeri: sebuah analisis morfologi - Dauty, Nisrina; Sofyan, Agus Nero; Sunarni, Nani; Soemantri, Yosi Soeria (Jurnal Pendidikan Bahasa dan Sastra, 2021)
This research is designed to be qualitative research with morphological approach, relying on the abbreviation theory as one of word formation process. Abbreviation is a shortening of the language term that occurs with the shortening of the lexeme. Any form of the abbreviation could be found in everyday life, especially in every daily national online news. Nevertheless, rests of the people only know the lexical meaning or contexts of every abbreviation that occur, without understanding how the abbreviations were arranged in linguistic point of view. The aim of this research is to describe the process of establishing abbreviation in every national online news with topics related to Covid-19. Abreviations related to covid-19 were the crucial object for this research. The method used is a method of listening and recording for data retrieval from national online news, and relying on Kridalaksana (2010)’s abbreviation theory and the General Guidelines for Spelling Bahasa Indonesia for the research analysis approach. The results suggest a form of abreviation in the form of abbreviations and contractions related to the Covid-19 pandemic. Shorthand abbreviation form found in this research were PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat), PSBB (Pembatasan Sosial Berskala Besar), OTG (Orang Tanpa Gejala), AKB (Adaptasi Kebiasaan Baru), and PJJ (Pembelajaran Jarak Jauh). Meanwhile, the forms of abreviation in the form of contractions are Satgas(Satuan Tugas), Prokes (Protokol Kesehatan) and Isoman (Isolasi Mandri).